Mobility Levels with Physical Rehabilitation Delivered during and after Extracorporeal Membrane Oxygenation (ECMO): A Marker of Illness Severity, or an Indication of Recovery?. Issue 12 (23rd December 2021) - Mayer, Kirby P; Pastva, Amy M; Du, Gaixin; Hatchett, Sarah P; Chang, Mingguang; Henning, Angela N; Maher, Baz; Morris, Peter E; Zwischenberger, Joseph B
Abstract: Objective: The aims of this study were to determine whether physical rehabilitation intervention for patients who required extracorporeal membrane oxygenation (ECMO) is associated with clinical outcomes and to assess whether the patient mobility response over initial rehabilitation sessions early in the intensive care unit (ICU) course predicts or is associated with survival, lengths of stay, discharge disposition, and 30-day readmissions. Methods: This study was a 10-year retrospective practice analysis of adults who were critically ill and required ECMO for >72 hours in the cardiothoracic ICU at an academic medical center. Physical rehabilitation implemented during or following the initiation of ECMO was quantified on the basis of timing, frequency, and change in mobility level in response to the intervention over the first 4 consecutive sessions. The primary dependent outcome was in-hospital mortality. Secondary outcomes included 30-day readmission and discharge disposition ranked on an ordinal scale. Results: Three hundred fifteen patients (mean age = 50 y [SD = 15 y]; 63% men; mean Sequential Organ Failure Assessment score = 11.6 [SD = 3.3]) met the inclusion criteria. Two hundred eighteen patients (69%) received at least 1 physical rehabilitation session while requiring ECMO, 70 (22%) received rehabilitation after ECMO was discontinued, and 27 (9%) never received rehabilitation. Patients discharged alive achieved higher mobility levels and had a steeper, more positive rate of change in mobility over the first 4 sessions than patients who died in the hospital (2.8 versus 0.38; t 199  = 8.24). Those who received rehabilitation and achieved the milestones of sitting on the edge of the bed and walking for>45 m were more likely to survive (47% versus 13%; χ 2  = 156) than those who did not (26% versus 3.5%; χ 2  = 80). Conclusion: A positive rate of change in mobility and the ability to achieve mobility milestones with rehabilitation were associated with improved clinical outcomes. Impact: A patient's mobility response to physical rehabilitation early in the ICU course is an important indicator of illness and should be used with clinical presentation to guide clinical decision making and predict outcomes.